Pengaruh Personal Branding, Kepuasan, dan Motivasi Terhadap Loyalitas Anggota Koperasai Simpan Pinjam di KOFIPINDO Unit 4 Medan Denai - Lawolo, Licerman; Aramita, Finta (Universitas Medan Area, 2024)
The objective to be achieved in this study is to determine how personal branding, satisfaction, and motivation affect the loyality of saving and loan cooperative members at KOFIPINDO unit 4 Medan Denai. The type of research used is an associative research type with a quantitative approach to determine the relationship between variables with a population of 850 people and with a number of samples used, namely 90 respondents through a questionnaire.. Based on the results of this study, it shows that: (1) personal branding (X1) has a positive and significant influence on loyality (Y) as evidenced by the calculated t value of 2,316 t table 1.987, (2) satisfaction (X2) has a positive and significant influence on loyality (Y) as evidenced by the calculated t value of 3.843 t table 1.987, (3) motivation (X3) has a positive influence on loyality (Y) as evidenced by the calculated t value of 9.053 t table 1.987, (4) the existence of a significant influence simultaneously between personal branding, satisfaction, and motivation on loyality can be seen through the calculated f table where the value is 100.388 6.163.